Assessment protocol of mesothelioma and relevance of SEM-EDS analysis through a case studies of legal medicine of Brescia (Italy). (July 2022) - Maghin, Francesca; Antonietti, Anna; Cerri, Nicoletta; Lancini, Liliana Maria; Maccarinelli, Andrea; Manzoni, Samuele; Restori, Mario; Rota, Matteo; Ruffini, Daniela; Verzeletti, Andrea; Conti, Adelaide
Highlights: This study evaluates the assessment protocol of mesothelioma with SEM-EDS. The quantity of asbestos fibres was evaluated by SEM. The SEM-EDS allows to identify the mineralogical species of each fibre. The microscopic analysis should be introduced in the evaluation protocol. Abstract: Introduction: This study evaluates the assessment protocol that allows the correlation between the development of mesothelioma to a specific exposure, with particular focus on investigations with Scanning Electron Microscope with Energy Dispersion Spectroscopy. Methods: This retrospective study includes 80 subjects who died from mesothelioma in the period 2001–2019. A judicial autopsy was performed for each case to confirm cause of death and correlate the disease with specific asbestos exposure. In 28 cases investigations were carried out to determine the pulmonary load of the asbestos fibres and corpuscles in the lung tissue through microscopic investigations, in order to confirm the suspicion of occupational exposure. Results: Our data agree with the scientific literature reported, but it is interesting to underline how the present study uses a different systematic approach than others, which are mainly based on epidemiological and environmental studies without considering the lung content of fibres and corpuscles. Conclusion: It would be desirable that the use of the microscopic analysis was introduced in the evaluation protocol: it should always be carried out if the suspicion of asbestos-related disease is raised and not only as a possible integration to the less expensive anamnestic evaluation, even more so if the work or personal history should be suggestive of exposure to asbestos fibres.